The influence of playing position and contextual factors on soccer players` match differential ratings of perceived exertion: A preliminary investigation - Barrett, S.; McLaren, S.; Spears, I.; Ward, P.; Weston, M. (Sports, 2018)
(1) Background: Differential RPE (dRPE) separates scores for breathlessness (RPE-B), leg muscle exertion (RPE-L) and technical/cognitive exertion (RPE-T). Limited information for dRPE is available in soccer match play, yet these measurements may help inform practitioners training and recovery strategies. This preliminary study investigated the effects of playing position and contextual factors on elite soccer players` dRPE. (2) Methods: Thirty-two male English Premier League players recorded dRPE scores 15-30 min post-match for RPE-B, RPE-L, and RPE-T. Data were analysed using linear mixed models, with magnitude-based inferences subsequently applied. (3) Results: Overall, the mean ± SD for the dRPE were 63 ± 23 arbitrary units (au) (RPE-B), 67 ± 22 au (RPE-L), and 60 ± 24 au (RPE-T). Full Backs reported substantially higher RPE-B, RPE-L and RPE-T when compared to all other positions. Substantially higher RPE-T scores were reported for matches played against Top teams compared to Bottom (10 au; 90% Confidence Interval 5 to 15 au) and Middle (10 au; 4 to 15 au) ranked teams. The effects of match result and location on dRPE were not substantial. (4) Conclusions: Positional differences were observed following soccer match play for RPE-B, RPE-L and RPE-T. Full backs had substantially higher dRPE then any other position, with all players reporting increased RPE-T when playing teams at the Top of the league. These findings can help practitioners monitor internal load responses and support the prescription of training and recovery sessions.